Tuning metal–support interactions on Ni/Al2O3 catalysts to improve catalytic activity and stability for dry reforming of methane - He, L; Ren, Y; Yue, B; Tsang, SCE; He, H (MDPI, 2021)
Ni-based catalysts supported on alumina derived from the pseudo-boehmite prepared by the impregnation method were employed for catalytic dry reforming of methane reaction at the temperature of 550–750 C. The effect of calcination temperature on physicochemical properties such as the Ni dispersion, reduction degree, nickel crystallite sizes, and metal–support interaction of the catalysts was investigated. The characterization results show that increasing the catalyst calcination temperature leads to the formation of nickel-alumina spinel, which enhances the metal–support interaction and increases the reduction temperature. The nickel nanoparticle size decreases and the effective dispersion increases with the increasing calcination temperature from 450 C to 750 C due to the formation of nickel aluminate. The catalyst calcined at 750 C exhibits the highest CH and CO conversion owing to the small Ni active sites and high Ni dispersion. In a 200 h stability test in dry reforming of methane at 700 C, the Ni/Al O -750 catalyst exhibits excellent catalytic stability and anti-coking ability.